Environmental enrichment reverses prenatal ethanol exposure-induced attention-deficits in rats - Wang, Ruixiang; Martin, Connor D.; Lei, Anna L.; Hausknecht, Kathryn A.; Richards, Jerry B.; Haj-Dahmane, Samir; Shen, Roh-Yu (Frontiers in Psychiatry, 2025)
IntroductionThere is a high prevalence of fetal alcohol spectrum disorders (FASD) in the US and the world, which is caused by prenatal ethanol exposure (PE). Most individuals with FASD show attention deficit hyperactivity disorder (ADHD) -like symptoms. Using a rat model of FASD, we have successfully demonstrated that moderate and heavy PE leads to persistent attention deficits, including augmented impulsivity and impaired sustained attention. Anxiety is another primary symptom of FASD. Anxiety and ADHD are closely associated in clinical studies. However, the causal relationship between anxiety and ADHD is not clear. In the present study, we used the strategy of environmental enrichment to reduce anxiety after PE in rats and investigated if attention deficits could be ameliorated.MethodsA 2nd-trimester binge-drinking pattern of heavy PE was used. Environmental enrichment consisted of neonatal handling and postweaning complex housing. Action impulsivity and sustained attention were tested in adult males and females using the 2-choice reaction time task.ResultsThe results show environmental enrichment effectively ameliorated action impulsivity and improved sustained attention in male and female PE rats. Action impulsivity was also improved in control rats with environmental enrichment. In addition, environmental enrichment improved the efficiency of obtaining rewards in male and female control but not PE rats. Environmental enrichment altered the pattern of reaction time components, favoring slower movement initiation but faster movement.DiscussionThese observations support that environmental enrichment could be an effective strategy in ameliorating ADHD-like symptoms in FASD. The reduced anxiety could contribute to such an effect.